2018
DOI: 10.1002/adsu.201800064
|View full text |Cite
|
Sign up to set email alerts
|

3D Heterostructured Copper Electrode for Conversion of Carbon Dioxide to Alcohols at Low Overpotentials

Abstract: to store intermittent renewable energy as well as closing the anthropogenic carbon cycle. [7,8] A wide array of metals, metal complexes, and hybrid catalysts based on Au, [9][10][11] Ag, [12][13][14] Sn, [15][16][17][18][19][20] Cu, [21][22][23] and Co [24][25][26] have been thoroughly investigated for CO 2 RR, however only Cu has been shown to generate ethanol and methanol with appreciable yield. Albeit, this unique property of Cu is also one of its major limitations as the metal produces numerous reduction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 71 publications
(85 reference statements)
1
39
0
Order By: Relevance
“…[39] It can be observed from Figure 4a, the intensity ratio between defects and the resonant A 1g phonon (I defect /I A1g ) was maximized for FSP-SnO 2 -5 (I defect /I A1g = 1.36) followed by FSP-SnO 2 -7 (I defect /I A1g = 1.25) and the lowest was for FSP-SnO 2 -3 (I defect /I A1g = 1.02). [44] It has been reported that OHC sites, alongside the radicals, assists in the binding of CO 2 reactants, [25,38,45] as well as active sites to stabilize the formate anion radical intermediate. UV-vis carried out with FSP-SnO 2 -5 further indicated that these defects are not changing the electronic states of the catalyst ( Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[39] It can be observed from Figure 4a, the intensity ratio between defects and the resonant A 1g phonon (I defect /I A1g ) was maximized for FSP-SnO 2 -5 (I defect /I A1g = 1.36) followed by FSP-SnO 2 -7 (I defect /I A1g = 1.25) and the lowest was for FSP-SnO 2 -3 (I defect /I A1g = 1.02). [44] It has been reported that OHC sites, alongside the radicals, assists in the binding of CO 2 reactants, [25,38,45] as well as active sites to stabilize the formate anion radical intermediate. UV-vis carried out with FSP-SnO 2 -5 further indicated that these defects are not changing the electronic states of the catalyst ( Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Zeng and co‐workers proposed an efficient strategy to facilitate CO 2 activation with surface‐rich oxygen vacancies in ZnO nanosheets by H 2 plasma treatment . The introduction of oxygen vacancies increases the charge density of ZnO resulting in the enhanced CO generation with j and maximum FE of −16.1 mA cm −2 and 83%, respectively at −1.1 V. Recently, oxygen vacancies on Cu‐based catalysts can be tuned toward electrocatalytic CO 2 reduction to generate ethylene and ethanol . Gu et al reported that partially reduced Cu oxide nanodendrites with surface‐rich oxygen vacancies serving as excellent Lewis base sites for enhanced adsorption of *CO 2 and the release of *CH 2 which were further hydrogenated to form ethylene .…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
“…The maximum FE C2H4 and its corresponding partial j are 63% and −18.5 mA cm −2 , respectively at operating potential of −1.4 V. Similarly, we also proposed a strategy to produce a unique three‐dimensional heterostructured Cu electrode via two‐step treatments including anodization and calcination. The as‐synthesized copper electrode can convert CO 2 to ethanol with FE of 31% and a stable current density of −1.3 mA cm −2 at low overpotential of −0.3 V . The enhanced activity of the electrocatalyst was attributed to the formation of abundant Cu + /Cu 2+ , which can be stabilized by the presence of oxygen vacancy defects.…”
Section: Active Sites In Metal‐based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations